Understanding Fathers’ Contribution to Behavioral Formation in Early Childhood: A Phenomenological Perspective - Annisa Wahyuni; Mastura Badzis; Sri Intan Wahyuni; Lina Amelia (HUMANISMA : Journal of Gender Studies, 2025)
This phenomenological study provides an in-depth examination of fathers' lived experiences in relation to early childhood behavioral development (ages 3–4) in Indonesia and Malaysia. The urgency of this research stems from the gap between the demands of contemporary parenting including digital literacy and the persistence of traditional masculinity constructs that often impede fathers' emotional involvement. Employing a qualitative phenomenological approach through in-depth interviews with four fathers of children aged 3–4 years, the core findings reveal that modern fathers have transitioned into vital agents of the Complementary Parenting Model. They specifically foster children's independence, resilience, and exploratory courage while simultaneously acting as digital gatekeepers through restrictive mediation practices. Theoretically, these results contribute to strengthening the Complementary Parenting Model. However, the study also highlights a significant challenge: the masculinity dilemma, which leads to difficulties in emotional regulation and affective communication (emotional literacy), often managed through rigid expressions of assertiveness. The study underscores the critical need to transform fathering education programs from mere awareness campaigns into comprehensive training initiatives that emphasize specific competencies, particularly consistent positive discipline and emotional literacy, to enhance the quality and effectiveness of paternal involvement in early childhood development.